Analisis Biaya Pemakaian Alat Berat Pada Proyek Rekontruksi Jalan Batas Kota Pariaman – Manggopoh Kabupaten Padang Pariaman Provinsi Sumatera Barat - Syauki, Ilham Ahmad; Iriana, Rian Trikomara; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research is aimed to analyze and identify the minimum cost of heavy equipment usage on the reconstruction Pariaman-Manggopoh border area Padang Pariaman Regency West Sumatera Province and to give the alternative manufacture and the effective enforcement method in the use of excavator. The calculation is analyzed using Bina Marga method. Based on the result, it is found that building the Aggregate Foundation Layer class A needs minimum cost Rp. 1.587.698.428,60 and building the Asphalt Pavement Layer needs minimum cost Rp. 4.954.643.081,75. The project enforcement can be done through several manufacture alternatives.Keywords : cost analysis, productivity, heavy equipment, and enforcement method